Injustice Management of Adat Land: Learn from Maranfenfen in Aru - Selvone Christin Pattiserlihun; Mustaqim Pabbajah; Ratri Nurina Widyanti (IAIN Ambon, 2023)
The issue of Adat (customary) land management carried out by the government as a ruler of indigenous peoples in the world is not a new thing to be discussed. Many phenomena of Adat land management deviate from human rights. This problem occurs because indigenous peoples still lack knowledge about laws and rights to Adat land. The State has strong control to regulate and take rights over all forms of natural wealth in Indonesia, including land because it is stated in the UUD NKRI 1945, Article 33 point 3